Randomised controlled trial of recombinant human growth hormone in prepubertal and pubertal renal transplant recipients. Issue 6 (1st December 1998) - Maxwell, H; Rees, L
Abstract : AIMS: To evaluate the efficacy (height velocity (HV), change in height standard deviation score (ΔHSDS)), and safety (glomerular filtration rate (GFR), incidence of rejection, and calcium and glucose metabolism) of recombinant human growth hormone (rhGH) treatment after renal transplantation. DESIGN: A two year randomised controlled trial. SUBJECTS: Fifteen prepubertal and seven pubertal children: mean (SD) age, 13.0 (2.6) and 15.2 (2.4) years, respectively; mean (SD) GFR, 51 (30) and 48 (17) ml/min/1.73 m 2, respectively. Six prepubertal and three pubertal children were controls during the first year; all received rhGH in the second year. RESULTS: In the first year, mean (SE) HV and ΔHSDS in the prepubertal treated group increased compared with controls: 8.1 (0.9) v 3.7 (0.6) cm/year and 0.6 (0.1) v −0.3 (0.2), respectively. In the pubertal treated group, mean (SE) HV and ΔHSDS were also greater: 10.1 (0.6) v 3.9 (1.3) cm/year and 0.6 (0.1) v −0.1 (0.2), respectively. Comparing all treated and control children, there was no significant change in GFR: treated group, mean (SE) 9.9 (5.4) ml/min/1.73 m 2 v control group, −1.6 (7.6) ml/min/1.73 m 2 . There were also no differences in the incidence of rejection in the first year: eight episodes in 13 patients v five episodes in nine patients, respectively. Phosphate, alkaline phosphatase (ALP), parathyroid hormone (PTH), and fasting insulin concentrations rose during the first year of treatment, but not thereafter. In the second year of treatment, HV remained above baseline. CONCLUSION: Treatment with rhGH improves growth in prepubertal and pubertal children with renal transplants, with no significant change in GFR or the incidence of rejection. Phosphate, ALP, PTH, and insulin increased during the first year of treatment.